Predictors of Relapse to Significant Alcohol Drinking after Liver Transplantation - Zamil Karim; Pongphob Intaraprasong; Charles H Scudamore; Siegfried R Erb; John G Soos; Elsie Cheung; Polly Cooper; Andrzej K Buzckowski; Stephen W Chung; Urs P Steinbrecher; Eric M Yoshida (Canadian Journal of Gastroenterology)
BACKGROUND: End-stage alcoholic liver disease is common, with many of these patients referred for liver transplantation (LT). Alcohol relapse after LT can have detrimental outcomes such as graft loss and can contribute to a negative public perception of LT.